The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/tmi.12419
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cord clamping in South African neonates with expected low birthweight: a randomised controlled trial

Abstract: Abstractobjective To evaluate safety and haematological effects of delayed cord clamping (DCC) in infants with expected low birthweight born in a resource-poor setting.methods Randomised controlled trial involving pregnant women in early labour ≥18 years with intrapartum symphysal-fundal height ≤32 cm. Mothers were randomised for either early cord clamping (ECC, <30 s) or DCC (2-3 min after birth).results We included 104 vigorous infants born by vaginal delivery, of whom 39% had a birthweight <2500 g. Infant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(40 reference statements)
1
9
0
2
Order By: Relevance
“…This descriptive analysis of malaria cases ex Eritrea notified to GeoSentinel shows that the majority of cases were P. vivax (84%) and the median time to presentation after arrival in the host country was 39 days (for those for whom data were available). These results mirror the findings of single centre studies in Europe [ 1 – 4 , 8 , 10 12 , 32 ]. and Israel [ 2 ] and reflect a shift in imported malaria species dominance in Europe due to the changing demographics of migrants and asylum seekers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This descriptive analysis of malaria cases ex Eritrea notified to GeoSentinel shows that the majority of cases were P. vivax (84%) and the median time to presentation after arrival in the host country was 39 days (for those for whom data were available). These results mirror the findings of single centre studies in Europe [ 1 – 4 , 8 , 10 12 , 32 ]. and Israel [ 2 ] and reflect a shift in imported malaria species dominance in Europe due to the changing demographics of migrants and asylum seekers.…”
Section: Discussionsupporting
confidence: 88%
“…In the Netherlands, during the period 2008–2015, P. vivax infections originated mainly from the Horn of Africa (214/372; 57.5%) and were largely attributable to asylum seekers from Eritrea [ 1 ]. In Milan, northern Italy, the proportion of P. vivax cases treated at a referral university hospital rose from 14.5% P. vivax in 2013 to 33.3% P. vivax in 2014 due mainly to malaria cases in Eritrean migrants [ 10 ]. In Sweden, a significant number of P. vivax cases in asylum-seekers from Eritrea led to the largest surge in imported malaria cases since computerized recording of malaria cases began in 1986 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ertekin et al [12] found that DCC up to 90–120 s increased the hemoglobin, hematocrit, and iron levels of infants significantly at the second month, but not at birth. Inversely, in a cohort of newborns with an expected low birth weight in South African, Tiemersma et al showed that the infant hemoglobin levels at 24 h after birth were significantly higher in the DCC group versus ECC group, while the effects of DCC on the infant hemoglobin levels were not detectable anymore at two months after birth [13].…”
Section: The Effect Of DCC On Hemoglobin Levels (Hb) In Term Infantsmentioning
confidence: 99%
“…In addition, despite successful placental transfusion, hyperbilirubinemia and hyperviscosity were not observed in South African neonates with expected low birth weight [13]. Garabedian et al [62] found that DCC resulted in no increase in severe hyperbilirubinemia in red blood cell alloimmunization.…”
Section: The Effect Of DCC On Jaundice and Requiring Phototherapy In mentioning
confidence: 99%
See 1 more Smart Citation